Study on the coexistence of Fagaceae in the evergreen broad-leaved forest of Malipo - LUO Rui; CHEN Xi; YANG Kehan (Xibei zhiwu xuebao)
[Objective] Investigating and analyzing the structure and dynamics of Fagaceae community in the subtropical evergreen broad-leaved forest of Malipo is important for exploring the coexistence mechanism and dominance of Quercus, Lithocarpus, and Castanopsis. This study provided an empirical study for understanding Fagaceae coexistence. [Methods] We set four 600 m2 plots in the Malipo natural reserve in May 2021. Excel 2019 and SPSS 25.0 software were used to analyze the dominant group by both individual number and basal area, and make static life table and survival curve to understand the differentiation among different genera and their coexistence mechanisms. [Results] (1) The average basal area of Fagaceae and Lithocarpus were 57.04% and 32.82%, which made them the dominant family and genera, respectively. (2) The diameter class distribution of the three genera was all barrel-shaped, with small proportion of seedlings and large trees (17.43%) and large proportion of small- and middle-sized trees (82.57%). (3) The survival curves of the three genera all fitted the Deevey-Ⅱ type. The mortality of Quercus and Castanopsis species was increased with increasing in diameter class, whereas after becoming saplings, Lithocarpus species become stablized. [Conclusion] Fagaceae, especially Lithocarpus, is the dominant group in the evergreen broad-leaved forests of Malipo. The differentiation in community dynamics, species distribution, and diversity among these three genera are important reasons for their coexistence and dominance.